Ecodesenvolvimento em comunidades rurais: análise por meio de indicadores sustentáveis - Oliveira, Mateus da Rosa (2024)
This qualitative study aims to deepen the analysis of Ecodevelopment in rural communities in Cascavel-PR. Under the theoretical mantle of Ignacy Sachs (1993), the research adopts a philosophical stance rooted in sustainability. To this end, it uses sustainable indicators meticulously selected from a specific reference, enriched by the systematics of Bardin (2015). The adapted model of Silveira (2003) stands out as an important tool for evaluating preconceived indicators, being adapted according to the specificities of the research locus. To achieve the proposed objectives, a case study was undertaken, using the Iramuteq software to decipher the interview transcripts, through the Descending Hierarchical Classification. In addition to these tools, interviews, observations, field diaries and documentary investigations were carried out. The methodological approach configures the research as descriptive, with primacy in the multiple case study. The results revealed that the economic and cultural dimensions presented the lowest rates in the context of Eco-development. On the other hand, the social dimension stood out as the most aligned with the precepts of the seminal theory. In addition, the territorial and environmental dimensions obtained similar results. However, even in the social dimension, certain indicators pointed to opportunities for improvements to be explored, as in the other dimensions. However, the research revealed singularities in the communities, such as the origin of the names, aspects little documented in academic records. As an academic contribution, this study proposes recommendations that aim to stimulate Eco development not only in the rural communities, the object of study, but also among the contextual agents that permeate the scenario. Thus, it seeks to catalyze the effective implementation of the pillars of the 2030 Agenda, notably the goals related to SDG-11, presenting society with a new perspective on these social entities, or rather, historical agents of agricultural development